Correction to: Finetuning Analytics Information Systems for a Better Understanding of Users: Evidence of Personification Bias on Multiple Digital Channels - Bernard J. Jansen (7434779) (2023)
Correction to: Finetuning Analytics Information Systems for a Better Understanding of Users: Evidence of Personification Bias on Multiple Digital Channels https://doi.org/10.1007/s10796-023-10395-5, published online 15 January 2024 The institutional affiliations for Bernard J. Jansen, Soon‑gyo Jung, and Joni Salminen were incorrectly listed on the first page of the original article. Bernard J. Jansen and Soon‑gyo Jung’s correct affiliation is Qatar Computing Research Institute, Hamad Bin Khalifa University, and Joni Salminen’s correct affiliation is School of Marketing and Communication, University of Vaasa. Other Information Published in: Information Systems Frontiers License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10796-023-10403-8